Drying banana seeds for ex situ conservation. Issue 1 (12th January 2022) - Kallow, Simon; Garcia Zuluaga, Manuela; Fanega Sleziak, Natalia; Nugraha, Bayu; Mertens, Arne; Janssens, Steven B; Gueco, Lavernee; Valle-Descalsota, Michelle Lyka; Dang Vu, Tuong; Toan Vu, Dang; Thi Li, Loan; Vandelook, Filip; et al.
Abstract : We investigated responses to drying for seeds of banana wild relatives to improve seed conservation for food security. We found that mature seeds were desiccation tolerant to levels required for seed genebanking but less mature seeds and those from unripe fruit that may be inadvertently collected have low viability and are sensitive to fast desiccation. Abstract: The ability of seeds to withstand drying is fundamental to ex situ seed conservation but drying responses are not well known for most wild species including crop wild relatives. We look at drying responses of seeds of Musa acuminata and Musa balbisiana, the two primary wild relatives of bananas and plantains, using the following four experimental approaches: (i) We equilibrated seeds to a range of relative humidity (RH) levels using non-saturated lithium chloride solutions and subsequently measured moisture content (MC) and viability. At each humidity level we tested viability using embryo rescue (ER), tetrazolium chloride staining and germination in an incubator. We found that seed viability was not reduced when seeds were dried to 4% equilibrium relative humidity (eRH; equating to 2.5% MC). (ii) We assessed viability of mature and less mature seeds using ER and germination in the soil and tested responses to drying. Findings showed that seeds must be fully mature to germinate and immature seeds had negligible viability. (iii) We dried seeds extracted from ripe/unripe fruit to 35–40% eRH at different rates and tested viability with germination tests in the soil. Seeds from unripe fruit lost viability when dried and especially when dried faster; seeds from ripe fruit only lost viability when fast dried. (iv) Finally, we dried and re-imbibed mature and less mature seeds and measured embryo shrinkage and volume change using X-ray computer tomography. Embryos of less mature seeds shrank significantly when dried to 15% eRH from 0.468 to 0.262 mm 3, but embryos of mature seeds did not. Based on our results, mature seeds from ripe fruit are desiccation tolerant to moisture levels required for seed genebanking but embryos from immature seeds are mechanistically less able to withstand desiccation, especially when water potential gradients are high.